Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1111/j.1365-2966.2005.09324.x
|View full text |Cite
|
Sign up to set email alerts
|

The VLT-UVES survey for molecular hydrogen in high-redshift damped Lyman α systems: physical conditions in the neutral gas

Abstract: We study the physical conditions in damped Lyman α systems (DLAs), using a sample of 33 systems towards 26 quasi-stellar objects (QSOs) acquired for a recently completed survey of H 2 by Ledoux, Petitjean & Srianand. We use the column densities of H 2 in different rotational levels, together with those of C I, C I * , C I * * , C II * and singly ionized atomic species to discuss the kinetic temperature, the density of hydrogen and the electronic density in the gas together with the ambient ultraviolet (UV) rad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
278
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(323 citation statements)
references
References 87 publications
40
278
4
Order By: Relevance
“…The column density, redshift, and b-parameter of each velocity component is given in Table 7. Note that Srianand et al (2005) derived log N(Si ii)= 14.86 ± 0.02 and log N(S ii)= 14.50 ± 0.02, where former is in good agreement with our result. B 2222-396, z abs =2.1539: the line profiles of this DLA are characterised by a simple velocity structure composed of two components.…”
Section: Notes On Individual Systemssupporting
confidence: 92%
See 1 more Smart Citation
“…The column density, redshift, and b-parameter of each velocity component is given in Table 7. Note that Srianand et al (2005) derived log N(Si ii)= 14.86 ± 0.02 and log N(S ii)= 14.50 ± 0.02, where former is in good agreement with our result. B 2222-396, z abs =2.1539: the line profiles of this DLA are characterised by a simple velocity structure composed of two components.…”
Section: Notes On Individual Systemssupporting
confidence: 92%
“…The properties of the velocity components are described in Table 1. Note that Srianand et al (2005) derived log N(S ii)= 14.30 ± 0.04, consistent to our results within the errors. The Si ii lines are either saturated or blended.…”
Section: Notes On Individual Systemssupporting
confidence: 92%
“…More importantly, the cold molecular gas can be missed due to relatively small cross-sections compared to the more pervasive warm neutral ISM (Zwaan & Prochaska 2006). Neutral carbon has been considered an excellent tracer of molecular hydrogen (H 2 ) because the ionization potential of C i (11.26 eV) is very close to the dissociation energy of H 2 (e.g., Srianand et al 2005). When H 2 is detected, C i is always present in the same system (e.g., Ge & Bechtold 1999;Ge, Bechtold, & Kulkarni 2001;Srianand et al 2008;Guimarães et al 2012;Noterdaeme et al 2015;Balashev et al 2017.)…”
Section: Das As Molecular Gas Tracersmentioning
confidence: 99%
“…Since the first identification of the H2 system in the quasar (Levshakov & Varshalovich 1985) other studies have been conducted, providing discordant results (see Table 2). Srianand et al (2005) used a two-component model, while King et al (2011) pointed out that a three-component model is very strongly preferred over two-component model. King et al (2011) used a fitting procedure where they increased the number of components in the absorption system in order to minimize the corrected Akaike information criterion, AICC 2 (Sugiura 1978;King et al 2011).…”
Section: Number Of Componentsmentioning
confidence: 99%
“…Molecular hydrogen absorption systems, a subset of damped Lyα systems (DLAs) and sub-damped Lyα systems (sub-DLAs), reveal diffuse and translucent interstellar clouds in high redshift intervening galaxies (Noterdaeme et al 2008). An analysis of H2 absorption systems allows for examining the physical conditions of diffuse clouds in distant galaxies (Srianand et al 2005;Noterdaeme et al 2007). It has been shown that the gas is a part of the cold neutral medium with comparatively low kinetic temperature (T ∼ 50 − 500 K) and high densities (nH > 10 cm −3 ), thus compact sizes (l < ∼ 1 pc).…”
Section: Introductionmentioning
confidence: 99%